Nuclear power plant instrumentation and control systems for safety and security - Yastrebenetsky, Michael, 1934-; Kharchenko, Vyacheslav, 1952- (Advances in environmental engineering and green technologies (AEEGT) book series., 2014)
"This book evaluates the risks inherent to nuclear power and methods of preventing accidents through computer control systems and other such emerging technologies"--